The Impact of Locus of Control on Budgetary Slack: Insights from The Literature Review - Mirza. BR, Aryan Danil (GOVERNORS, 2025)
Budgetary slack is a prevalent issue in managerial accounting, often linked to individual behavioral tendencies. On the other hand, Locus of control has emerged as a significant factor influencing budgeting behavior. This study explores the relationship between locus of control and budgetary slack through a literature review approach. We Use Scopus, Web of Science and Google Scholar database using keyword “locus of control” and “budgetary slack”.  The review indicates that individuals with an internal locus of control are generally less likely to create budgetary slack due to their intrinsic motivation, sense of responsibility, and goal alignment with the organization. In contrast, those with an external locus tend to manipulate budgets as a means of protection or strategic advantage, especially under conditions of uncertainty or perceived injustice. The study underscores the importance of integrating psychological insights into budgeting processes and suggests that organizations can mitigate dysfunctional budgeting behavior by fostering environments that support accountability, trust, and participation. Ultimately, this research contributes to the field of behavioral accounting by providing a theoretical foundation for understanding how personality traits interact with organizational controls to shape budgeting outcomes.